Faktor Internal dan Eksternal yang Mempengaruhi Tingkat Resistensi Petani Terhadap Usahatani Padi Organik - Muhammad Hardika Prasetya; Damara Dinda Nirmalasari Zebua; Yuliawati Yuliawati (Jurnal Sosial Ekonomi Pertanian, 2021)
This study aims to know the level of resistance of farmers and the factors that affect the level of resistance of farmers to organic rice farming in the Boyolali Organic Farmers Association (APOB). This is descriptive quantitative research. Data collected by interviewing with a questionnaire to 88 farmers who are members of APOB and not yet or not applying organic rice farming. Internal factors in this study are knowledge, skills, attitudes and subjective norms, while external factors consist of social environment and economic environment. Data analysis used descriptive analysis and multiple linear regression. The results showed that: 1) the level of resistance of farmers was classified into moderate resistance because farmers carried out processing and fertilization approaching organic, while the use of seeds, pesticides and integrated pest management (IPM) still tended to approach conventional. Perceptions of farmers who are resistant to organic rice farming include a greater risk of organic rice farming, greater capital spent and too complicated regulations; 2) Internal factors that affect the level of farmer resistance are skills and subjective norms, while the external factors that influence is economic environment. Keywords: Boyolali Organic Farmers Association (APOB), Resistance Factors, Resistance Levels, Organic Rice Farming.